Time Waste at Specialist Clinic Service of Primasatya Husada Citra (PHC) Hospital Surabaya - Mulyawan, Indra; Kurniawan, Rony; Wardhani, Viera (Jurnal Kedokteran Brawijaya, 2022)
Waiting time in outpatient services is a factor that causes patient dissatisfaction and affects hospital image. The standard waiting time for outpatient services in hospitals, starting from the registration until the end of the doctor's examination, is 60 minutes. This study was conducted to identify time waste in the registration process of outpatient services. This descriptive study was done at the Specialist Clinic of Primasatya Husada Citra Hospital (PHC Hospital) Surabaya. The time waste identification on waiting time was carried out using the Value Stream Mapping (VSM) method using observation data at PHC Hospital, which were categorized as defect, overproduction, waiting, non-utilized talent, transportation, inventory, motion, and extra processing. Activities carried out were identified and grouped into categories, namely waiting, service, and transport document, and then reclassified into value added, non-value added, and necessary non-value added. The results show that the waiting time wastes were waiting after verification (± 60.2 minutes), filling out e-RM (± 139.6 minutes), and waiting for the doctor to come.